Research in global strategic management. Vol. 4 - Rugman, Alan M.; Verbeke, Alain (Emerald, 1994)
Part of a series which presents research on global strategic management, this volume focuses on the corporate response to global change. Topics discussed include the foundations of global strategy, extensions of porters generic strategies and shelter bases strategies.
Keywords: International business enterprises -- Management.; Strategic planning.; Global economics.; elektronické knihy; electronic books